Promotion of couples' voluntary HIV counselling and testing in Lusaka, Zambia by influence network leaders and agents. Issue 5 (6th September 2012) - Wall, Kristin M; Kilembe, William; Nizam, Azhar; Vwalika, Cheswa; Kautzman, Michelle; Chomba, Elwyn; Tichacek, Amanda; Sardar, Gurkiran; Casanova, Deborah; Henderson, Faith; Mulenga, Joseph; Kleinbaum, David; et al.
Abstract : Objectives: Hypothesising that couples' voluntary counselling and testing (CVCT) promotions can increase CVCT uptake, this study identified predictors of successful CVCT promotion in Lusaka, Zambia. Design: Cohort study. Setting: Lusaka, Zambia. Participants: 68 influential network leaders (INLs) identified 320 agents (INAs) who delivered 29 119 CVCT invitations to heterosexual couples. Intervention: The CVCT promotional model used INLs who identified INAs, who in turn conducted community-based promotion and distribution of CVCT invitations in two neighbourhoods over 18 months, with a mobile unit in one neighbourhood crossing over to the other mid-way through. Primary outcome: The primary outcome of interest was couple testing (yes/no) after receipt of a CVCT invitation. INA, couple and invitation characteristics predictive of couples' testing were evaluated accounting for two-level clustering. Results: INAs delivered invitations resulting in 1727 couples testing (6% success rate). In multivariate analyses, INA characteristics significantly predictive of CVCT uptake included promoting in community-based (adjusted OR (aOR)=1.3; 95% CI 1.0 to 1.8) or health (aOR=1.5; 95% CI 1.2 to 2.0) networks versus private networks; being employed in the sales/service industry (aOR=1.5; 95% CI 1.0 to 2.1) versus unskilled manual labour; owning a home (aOR=0.7; 95% CI 0.6 to 0.9) versus not; and having tested for HIV with a partner (aOR=1.4; 95% CI 1.1 to 1.7) or alone (aOR=1.3; 95% CI 1.0 to 1.6) versus never having tested. Cohabiting couples were more likely to test (aOR=1.4; 95% CI 1.2 to 1.6) than non-cohabiting couples. Context characteristics predictive of CVCT uptake included inviting couples (aOR=1.2; 95% CI 1.0 to 1.4) versus individuals; the woman (aOR=1.6; 95% CI 1.2 to 2.2) or couple (aOR=1.4; 95% CI 1.0 to 1.8) initiating contact versus the INA; the couple being socially acquainted with the INA (aOR=1.6; 95% CI 1.4 to 1.9) versus having just met; home invitation delivery (aOR=1.3; 95% CI 1.1 to 1.5) versus elsewhere; and easy invitation delivery (aOR=1.8; 95% CI 1.4 to 2.2) versus difficult as reported by the INA. Conclusions: This study demonstrated the ability of influential people to promote CVCT and identified agent, couple and context-level factors associated with CVCT uptake in Lusaka, Zambia. We encourage the development of CVCT promotions in other sub-Saharan African countries to support sustained CVCT dissemination.